1993
DOI: 10.1103/physrevlett.71.4393
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a spin liquid in a two dimensional quantum antiferromagnet

Abstract: The ground state properties of the two dimensional spatially anisotropic Heisenberg model are investigated by use of field theory mappings, spin-wave expansion, and Lanczos technique. Evidence for a disorder transition induced by anisotropy at about Jy/Jx < 0.1 is shown. We argue that the disordered phase is gapless and its long wavelength properties can be interpreted in terms of decoupled one dimensional chains.PACS numbers: 75.10.Jm, 75.30.Ds The search for disordered (spin liquid) ground states in two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
56
5

Year Published

1994
1994
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 22 publications
5
56
5
Order By: Relevance
“…Previously, it was proposed that there is a non-zero critical coupling ratio (J ′ /J = R c ), below which the system retains a singlet ground-state [5]. Recent renormalization group calculations however suggest that the ground state may depend on microscopic details of the model which describes the spin-spin interactions [6,7].…”
mentioning
confidence: 99%
“…Previously, it was proposed that there is a non-zero critical coupling ratio (J ′ /J = R c ), below which the system retains a singlet ground-state [5]. Recent renormalization group calculations however suggest that the ground state may depend on microscopic details of the model which describes the spin-spin interactions [6,7].…”
mentioning
confidence: 99%
“…It has been proposed that the system can be described in terms of a short-range resonating valence bond (RVB) picture [6,8], and mean field treatments with Gutzwiller renormalization of the matrix elements have supported this conclusion. It has also been suggested that in contrast, systems with an odd number of chains n c are gapless [7,8].…”
mentioning
confidence: 99%
“…A number of studies [3][4][5][6][7][8] have provided strong evidence that at half-filling the two-chain ladder systems are spin liquids, with a spin-gap and finite spin-spin correlation length. It has been proposed that the system can be described in terms of a short-range resonating valence bond (RVB) picture [6,8], and mean field treatments with Gutzwiller renormalization of the matrix elements have supported this conclusion.…”
mentioning
confidence: 99%
“…This should be compared with the spin wave value for the square case 16 , J ⊥ /J ∼ 0.03, where the difference in one order of magnitude shows that the way in which fluctuations overcome the ordering is different. However, in the regime around η = 1 the spin wave calculation is not reliable any more since quantum fluctuations are divergent in the 1D limit.…”
mentioning
confidence: 99%